Impact of tire particle leachates on microplankton communities in the Canary Islands - Marta Sampalo; May Gómez; Rodrigo Almeda (Ecotoxicology and Environmental Safety)
Tire wear particles (TWP) are a major source of microplastics in the environment. Despite their prevalence, the effects of tire particle leachates on marine microplankton communities remains poorly understood. In this study, we assessed the acute impacts of tire particle leachates on the structure of coastal microplankton assemblages from the Canary Islands. Five laboratory experiments were conducted, exposing microplankton to a range of leachate dilutions over 72 h, with TWP leachates prepared from an initial concentration of 1 g L⁻¹ .Our results revealed that the abundances of diatoms, most dinoflagellates, and ciliates were significantly reduced following exposure to leachates, with median effective concentrations (EC50) ranging from 30 to 660 mg L−1 depending on the plankton community. Interestingly, Ostreopsis cf. ovata, a harmful algal bloom (HAB)-forming species, exhibited relatively high tolerance to tire particle leachates compared to other microplankton. Compared to other marine biota, ciliates appear to be most vulnerable plankton group to tire particle leachates (EC50 = 30 and 146 mg L−1). The higher tolerance of O. cf. ovata to pollution compared to other phytoplankton species (resource competitors), in combination with other factors, may contribute to the rise of HABs in polluted coastal areas. Although field data on TWP are limited, the observed negative effects on microplankton occurred at environmentally relevant concentrations. Our results indicate that TWP pollution can significantly impact marine planktonic communities, highlighting the urgent need to reduce TWP emissions and develop less toxic tire rubber additives.